Dramatic Space: Translating Euripides’ Medea into Lithuanian, Latvian, and Estonian - Dikmonienė, Jovita; Bodniece, Līva; Lotman, Maria-Kristiina (Semiotika, 2024)
This article analyzes the translations of Euripides’ Medea into Lithuanian, Estonian and Latvian languages. It investigates how translators convey or adapt the original space of ancient theatre and drama in the meta-discourse and discourse of tragedy. The article has three main parts devoted to Benediktas Kazlauskas’ Lithuanian translation, Augusts Ģiezens’ Latvian translation, and Tiit Palu’s Estonian adaptation. Each part is divided into subsections, where the mimetic and diegetic space of ancient drama, stage directions, and objects of space: house, bed, and door are analyzed. The meta-discourse of Kazlauskas and Ģiezens is compared to the English translation by David Kovacs. The study examines what new symbolic meanings Euripides assigns to spatial objects and how he reinterprets the meanings of home as a place of security and family, giving it new connotations. The article concludes that the translations of Euripides’ Medea from the three Baltic countries represent the dramatic space differently because the translators adhere to different ideologies. The philological translations of Kazlauskas and Ģiezens are similar due to the rendering of the ancient meter and are focused on the reader, while Tiit Palu’s adaptation is made for the theatre. Kazlauskas calls Medea’s house a “palace”, giving the space epicness, solemnity and formality. It can also be seen that his euphemistic language reflects the censorship of the Soviet era – not to translate words denoting the sexual sphere. Ģiezens’ translation into Latvian emphasizes the personal and intimate aspects of the drama. Tiit Palu’s Estonian adaptation focuses on the psychological depth of the drama, partially preserving the spatial and architectural integrity of the original while contextualizing ancient myth in the contemporary situation to make it more accessible for a modern audience. Each translator adapts the dramatic space to suit cultural contexts, balancing fidelity to Euripides’ original with accessibility to modern readers and audiences.